Viajes paralelos desde el mito de Aracné: Los abismos interiores de Aline Pettersson - García Peña, Lilia Leticia (Amaltea. Revista de Mitocrítica, 2010)
Aline Pettersson is a renamed Mexican writer who was born in 1938. In this work I analize the representation of the myth of Aracne in her text Viajes paralelos (2002) through the presence of three the knitting, tapestry and the spider, from which the text goes through the artistic creation process and seeks to conjure time’s fragility towards its transfiguration in a mythic time.